Effects of Serbian Accession to the European Union - Holzner, Mario; Ivanić, Valentina (Panoeconomicus, 2012)
In this article, the global simulation model (GSIM) of Joseph F. Francois and Keith H. Hall (2009) for analyzing global, regional, and unilateral trade policy changes was applied to Serbia. This was to measure the effects of full trade liberalization with the EU after Serbian accession to the EU. As anticipated, most of the changes in welfare after full liberalization of trade between Serbia and EU can be expected in sectors where Serbia has specialized; protection against imports from the EU is strong. However, losses could also occur in sectors that currently face strong protection against the rest of the world and this protection is lost after EU accession. Trade liberalization will lead to a substantial loss of tariff revenues. Reduced consumer prices might, on the one hand increase consumer surplus but on the other hand decrease producer surplus and output in certain industries. Key words: Cost of protection, Partial equilibrium model, Trade policy modelling, Serbia. JEL: F13, F15, F17.